Revising the geological mapping of Mars - Marco Pantaloni (mediaGEO soc. coop., 2019)
Planetary geological-geomorphological mapping has some peculiarities which need to be addressed in order to standardize the technical and scientific approach. The aim of this project is the attempt to apply the cartographic standards rules used in the Italian Geological Mapping Project (CARG Project) for the realization of geological and geomorphological maps at various scales of detail even in the planetary environment.